Photon energy and photon behavior discussions - Daocheng Yuan (Elsevier, 2022)
Photons (Solar) are the main source of energy available on Earth and provide hope of clean energy in the future, photon energy has particle characteristics, and there is an inevitable connection between the wave behavior and the particle behavior of light, in-depth understanding and exploration are required. Based on the hypothesis of the strong interaction between electrons and protons to generate photons, the energy and behaviors of photons are discussed herein. By analyzing and calculating the photon speed, the negative photon speed was found to be in excellent agreement with the existing light speed constant. The Compton effect wavelength shift was analyzed and deduced considering the interaction of positive photons and atoms, and new conclusions are drawn, proposing the reason why X-rays are positive photons. Based on existing data, the observed estimation value of the negative photon velocity shift is 0.0295 ppm. From the interaction of the spin-charged particles, the relationship between the photon wavelength and its magnetic moment was calculated. In addition, we analyzed and calculated the characteristics of photon orbits, inferred the mechanism of atomic luminescence, and qualitatively explained the phenomenon of blackbody radiation. Based on the effect of charged spin photons and the electromagnetic potential field, we explain the reason for the simultaneous existence of reflection and refraction. The relationship between the incident angle and the reflectivity was analyzed, and refractive index formulas were derived to reasonably explain the characteristics of the X-ray refractive index. As a result, edge diffraction is considered a special case of refraction. By analyzing the fluctuation of the potential field inside the atom, the diffraction phenomenon of charged particles is described, and a particle explanation of the phenomenon of light waves and beat frequencies interference is provided. It is believed that the physical model of photon charging conforms to the existing physical laws. Photon energy is kinetic energy and is derived from the potential energy of electrons or protons.